Free-weight resistance training enhances core muscle strength but does not translate to improved athletic performance in adolescent Canoe/Kayak athletes - Lee, T.-T.; Ko, B.-J.; Chang, C.-H.; Cheng, I.-S. (Children, 2024)
Background/Objectives: While previous evidence has shown that using free weights for resistance training is a more practical approach to enhancing strength, there is a relatively low prevalence of free-weight resistance training among adolescent kayak/canoe athletes. Therefore, this study aims to assess the impact of free-weight resistance training on body composition and various performance factors among adolescent canoe/kayak athletes.